Congenital and Traumatic Conditions of the Pediatric Hand: Overview for the Radiologist - Kan, J. Herman; Barron, Olivia A.; Bell, Bryce R. (Seminars in Musculoskeletal Radiology, 2024)
Alignment, longitudinal growth, and function of the musculoskeletal unit of the pediatric hand is complex due to the combination of open growth plates, ossification variations, and their relationship with finger tendinous and ligamentous attachments. This review presents the basics of normal development, acquired and congenital variations, and traumatic conditions of the pediatric hand from the perspective of the pediatric musculoskeletal radiologist and hand surgeon. This multimodality imaging article focuses on non-oncologic and non-rheumatologic conditions of the pediatric hand, inclusive of fingers, thumb, and metacarpal bones.
Keywords: radiographs; ultrasonography; congenital hand deformities; traumatic hand deformities; bone age